Shift work and risk factors for coronary heart disease in Japanese blue-collar workers: Serum lipids and anthropometric characteristics - Kazutoshi Nakamura; S. Shimai; S. Kikuchi; Kana Tominaga; Hidekatsu Takahashi; Masatoshi Tanaka; Shin‐ichi Nakano; Yutaka Motohashi; Hiroto Nakadaira; Masahiko Yamamoto (1997)
This study was conducted to determine if there is an association between shift work and risk factors for coronary heart disease (CHD) in Japanese mate blue-collar shift workers. Health check-up data on serum lipid concentration and anthropometric indices of 33 three-shift workers and 27 two-shift workers were compared with those of day workers. The average years in age of the shift workers and day workers were 34.5 (SD=7.1) and 32.7 (SD=7.6), respectively. Serum total cholesterol levels of three-shift, two-shift and day workers were 5.70 (SD=1.19) mmol/l, 4.81 (SD=1.01) mmol/l, 4.98 (SD=0.95) mmol/l, respectively, and the cholesterol levels of three-shift workers were significantly higher than the other workers (p<0.05). In addition, the abdominal to hip circumference ratios were 0.905 (SD=0.060) for three-shift workers and 0.877 (SD=0.054) for day workers, with a significant difference (p<0.05). In the present Japanese population, three-shift workers had higher risks of CHD than day workers, which was characterized by higher levels of serum total cholesterol and tendency to central obesity. These findings held when lifestyle factors were taken into account.